Islamic arms and armor in the metropolitan museum of art - Alexander, David G.; Pyhrr, Stuart W.; Kwiatkowski, Will; Metropolitan Museum of Art (New York, N.Y.). Department of Arms and Armor (New York : The Metropolitan Museum of Art, 2015)
'From its origins in the 7th century, armor and weaponry were central to Islamic culture not only as a means of conquest and the spread of faith, but also as symbols of status, wealth, and power. More than 120 exceptional examples from the renowned collection of The Metropolitan Museum of Art are presented in detail to demonstrate the remarkable craftsmanship and beauty of Islamic arms and armor. These diverse objects, which have never been catalogued or published in detail, span ten centuries and represent nearly every Islamic culture, from Spain to the Caucasus. Among these masterpieces are rare early works, such as the oldest documented Islamic sword, and fine examples of decorated helmets and body armor from late-15th-century Iran and Anatolia. Also included are lavish gem-studded weapons from royal courts in the Ottoman world and India. Each piece is handsomely photographed, with a detailed discussion of its technical, historical, and artistic importance. Made by master artisans in conjunction with leading designers, goldsmiths, and jewelers, these stunning objects demonstrate how utilitarian military equipment could be transformed into striking and extravagant works of art.'--YaleBooks website
'Armor and weaponry were central to Islamic culture not only as a means of conquest and the spread of the faith, but also as symbols of status, wealth, and power. The finest arms were made by master craftsmen working with the leading designers, goldsmiths, and jewelers, whose work transformed utilitarian military equipment into courtly works of art. This book reveals the diversity and artistic quality of one of the most important and encyclopedic collections of its kind in the West. The Metropolitan Museum's holdings span ten centuries and include representative pieces from almost every Islamic culture from Spain to the Caucasus. Presenting 126 objects, each handsomely photographed and richly documented with a detailed description of discussion of its technical, historical, and artistic importance, this overview of the Met's holdings is supplemented by an introductory essay on the formation of the collection, and appendixes on iconography and on Turkman-style armor.' -- Publisher's description
American collectors and the formation of the Metropolitan Museum's collection of Islamic arms and armor / Stuart W. Pyhrr --Catalogue / David G. Alexander. Armor : Mail and plate armor (cats. 1-18) ; Helmets (cats. 19-43) ; Shields ; (cats. 44-46) ; Horse armor (cats. 47-53) --Edged weapons : Swords and sabers (cats. 54-74) ; Daggers (cats. 75-92) ; Shafted weapons (cats. 93-107) --Firearms and archery : Firearms (cats. 108-123) ; Archery (cats. 124-126) --Appendix A: comments on iconography and decoration on Islamic arms and armor / David. G Alexander --Appendix B: Turkman-style armor / David G. Alexander.
Includes bibliographical references (pages 312-329) and index.
Sumbangan Mohamad Taha (2017).
Keywords: Metropolitan Museum of Art (New York, N.Y.). Department of Arms and Armor -- Catalogs; Islamic weapons -- Catalogs; Islamic armor -- Catalogs